Rola przepływu wdechowego w optymalnej technice inhalacji z DPI i metody jego pomiaru = Role inspiratory flow at optimal inhalation with a DPI technology and its methods of measurement - Czerwińska Pawluk, Iwona; Markut–Miotła, Ewa (Journal of Education, Health and Sport, 2015)
Czerwińska Pawluk Iwona, Markut–Miotła Ewa. Rola przepływu wdechowego w optymalnej technice inhalacji z DPI i metody jego pomiaru = Role inspiratory flow at optimal inhalation with a DPI technology and its methods of measurement. Journal of Education, Health and Sport. 2015;5(1):284-292. ISSN 2391-8306. DOI: http://dx.doi.org/10.5281/zenodo.44483 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A284-292 https://pbn.nauka.gov.pl/works/689292 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2015. Revised 18.01.2015. Accepted: 21.01.2015. ROLA PRZEPŁYWU WDECHOWEGO W OPTYMALNEJ TECHNICE INHALACJI Z DPI I METODY JEGO POMIARU ROLE INSPIRATORY FLOW AT OPTIMAL INHALATION WITH A DPI TECHNOLOGY AND ITS METHODS OF MEASUREMENT Iwona Czerwińska Pawluk Radomska Szkoła Wyższa w Radomiu , Wydział Nauk o Zdrowiu Uniwersytecki Szpital Dziecięcy, Lublin ul. Prof. A. Gębali 6 Ewa Markut–Miotła Katedra i Zakład Pielęgniarstwa Pediatrycznego Uniwersytetu Medycznego w Lublinie Streszczenie Ważne miejsce w terapii schorzeń układu oddechowego zajmują inhalatory suchego proszku (DPIs). Na wielkość depozycji płucnej leków podawanych z DPIs wpływają czynniki zewnętrzne oraz czynniki zależne od pacjenta. Pośród czynników zależnych od pacjenta szczególne znaczenie ma technika inhalacji, w tym wielkość i jakość wysiłku wdechowego, rodzaj patologii i stan czynnościowy układu oddechowego. Jednym z parametrów opisujących wdech chorego jest szczytowy przepływ wdechowy – PIF. Wielkość PIF jaką pacjent jest w stanie wygenerować zależy od: wieku pacjenta, stanu fizycznego dróg oddechowych i mięśni wdechowych oraz stanu czynnościowego układu oddechowego. Na wartość PIF wpływa też świadome działanie pacjenta. Wielkość PIF konieczna do aerolizacji i zainhalowania właściwej dawki leku o optymalnym składzie cząstek jest różna dla poszczególnych DPIs. Głównym czynnikiem determinującym to zjawisko jest opór wewnętrzny danego DPI, co z kolei decyduje o ciśnieniu powietrza przechodzącego przez urządzenie i o jego przepływie. Przepływ wdechowy i inne parametry opisujące wysiłek wdechowy ocenia się przy pomocy metod: ilościowych, półilościowych i jakościowych (orientacyjnych). Słowa kluczowe: inhalatory suchego proszku (DPIs), szczytowy przepływ wdechowy (PIF). Abstract Dry powder inhalers (DPIs) play an important role in the therapy of respiratory track diseases. Lung deposition via DPI can affect external and patient -related factors. Particularly important among patient-related elements is an inhalation technique, including quantity and quality of respiratory effort, type of pathology and lung function parameters . One of the parameters describing inspiration maneuver of a patient is peak inspiratory flow-PIF. PIF value generated by an individual depends on: age, inspiratory muscles condition, lung physical and function parameters. Patient’s conscious action also influence on PIF value. PIF necessary for aerolisation and inhaled drug delivery (proper dose of optimal particle) differ between DPIs devices. Main factor determining this proces is internal resistence of each DPI device , which indicates air pressure and airflow through DPI device. Inspiration flow and other parameters describing inspiration effort can be measured by quantitive, semi-quentitive and qualitive methods. Key words: dry powder inhalers (DPIs), peak inspiratory flow (PIF).